EUPATI Guidance for Patient Involvement in Medicines Research and Development: Health Technology Assessment - Hunter, Amy; Facey, Karen; Thomas, Victoria; Haerry, David; Warner, Kay; Klingmann, Ingrid; May, Matthew; See, Wolf (Frontiers in Medicine, 2018)
The main aim of health technology assessment (HTA) is to inform decision making by health care policy makers. It is a systematic process that evaluates the use of health technologies and generally involves a critical review of international evidence related to clinical effectiveness of the health technology vs the best standard of care. It can also include an evaluation of cost effectiveness, and social and ethical impacts in the local health care system.